TYPE 2 DIABETES MELLITUS’ PATIENT ANXIETY : STUDY LITERATURE REVIEW (UPPM. Poltekkes Kemenkes Bandung, 2022)
According to the Ministry of Health of the Republic of Indonesia in 2018 the prevalence of DM in West Java has increased. DM patients including T2DM have a high level of psychological stress due to their illness. That is because T2DM patients experience sudden life changes. If not managed properly can lead to various complications. T2DM and its complications bring huge losses to patients and their families, make patients incur more costs, and increase anxiety about their future. This study aims to determine the anxiety level of T2DM patients. The research method used is the study of literature. Research results from 5 research journals showed that almost half (44.7%) of T2DM patients experienced normal anxiety levels, more than half (65.5%) of T2DM patients experienced mild anxiety levels, more than half (56.7%) T2DM patients experience moderate anxiety levels, and more than half (55.3%) T2DM patients experience severe anxiety levels. Thus, the majority of T2DM patients experience anxiety. It is recommended to nurses to intervene in overcoming the anxiety of T2DM patients. Especially nurses or other health professions do health education on how to deal with anxiety, especially the anxiety of T2DM patients.